Serum cytokines to predict systemic lupus erythematosus clinical and serological activity - Victor Moreno‐Torres; Raquel Castejón; María Martínez‐Urbistondo; Ángela Gutiérrez‐Rojas; Jose Vázquez‐Comendador; Pablo Tutor; Pedro Durán‐del Campo; Susana Mellor‐Pita; Silvia Rosado; Juan‐Antonio Vargas‐Núñez (Wiley, 2022)
Abstract We aimed to explore the role of interleukin (IL)‐6, interferon‐gamma (IFNγ), IL‐10, and tumor necrosis factor (TNF) as predictors of systemic lupus erythematosus (SLE) clinical and serological activity, and their correlation with the treatment received. We performed a retrospective analysis of 77 patients with SLE according to the 2012 Systemic Lupus International Collaborative Clinics (SLICC) criteria. The outcomes were serological activity (SA), active disease (AD), complete remission (CR), the low‐disease activity state (LDAS), and immunosuppressive treatment. SA was present in 17.1%, AD in 17.3%, CR in 13%, and LDAS in 64.9% of patients. IL‐6 values were higher in patients in SA, in AD, in those receiving steroids alone, and in patients without CR or LDAS (p < 0.05). IFNγ was associated with anti‐double stranded DNA (dsDNA) antibodies positivity and immunosuppression, whereas IL‐10 values were higher in patients with CR (p < 0.05). The IL6‐IFN product was able to predict anti‐double stranded DNA (anti‐dsDNA) antibodies positivity (area under the receiver operating characteristic curve [AUC‐ROC] = 0.705, 95% confidence interval [CI] 0.563-0.847), SA (AUC‐ROC = 0.720, 95% CI 0.542-0.899), AD (AUC‐ROC = 0.701, 95% CI 0.520-0.882), steroid treatment (AUC‐ROC = 0.751, 95% CI 0.622-0.879), and the absence of LDAS (AUC‐ROC = 0.700, 95% CI 0.558-0.834). The IL6‐IFN/IL10 ratio predicted AD (AUC‐ROC = 0.742, 955 CI 0.540-0.944), steroid treatment (AUC‐ROC = 0.721, 95% CI 0.572-0.870), and the absence of LDAS (AUC‐ROC = 0.694, 95% CI 0.536-0.853). In conclusion, IL‐6, IL‐10, and IFNγ might help to assess SLE serological and clinical activity. Their combination in the IL‐6‐IFN product and the IL‐6xIFN to IL‐10 ratio results in novel tools to determine and predict SA, AD, and LDAS. Prompt detection of SLE activity might allow a rapid intervention to avoid established or chronic damage.